Rise of 'Rizz': A Morphological Study of Its Formation and Usage - Purba, Christian Neni; Nainggolan, Adika Indotua (Innovative: Journal Of Social Science Research, 2025)
This study examines the slang word "rizz" from a morphological perspective, analyzing its formation, evolution, and impact on contemporary language. Emerging from digital platforms, "rizz" was first popularized by Twitch streamer Kai Cenat and has since gained widespread recognition, culminating in its selection as Oxford’s Word of the Year in 2023. Using a descriptive qualitative approach, this research explores the structural properties of "rizz," identifying it as a clipped form of "charisma" and highlighting its functional shift from a noun to a verb. The study further investigates the role of digital media in the rapid dissemination of slang and how online communities influence language change. Findings suggest that "rizz" exemplifies the dynamic nature of modern slang, demonstrating linguistic creativity and social adaptability. The paper concludes by discussing the broader implications of digital slang in shaping linguistic trends and suggests further research into the longevity and mainstream integration of internet-originated terms.